Peranan Repurchase Intention dalam Memediasi Pengaruh Customer Experience dan Trust: Perspektif Loyalitas Konsumen pada E-Market Place - Budi, M. Arief Setia (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to influence customer experience and trust on repurchase intention e-market place and its impact on consumer loyalty: a case study on shopee. The population in this study were all Shopee consumers in Banda Aceh City. The sample collection technique in this study was purposive sampling. So that the number of respondents was 250 people. Data were collected by distributing questionnaires online which were linked to a google form. Data were measured using a Likert scale and analyzed using SEM AMOS. The test results concluded that Customer Experience, Trust, Repurchase Intention, and Shopee Consumer Loyalty on Shopee were running well; Customer experience affects repurchase intention; Trust affects repurchase intention; Customer experience affects consumer loyalty; Trust affects consumer loyalty; Repurchase intention affects consumer loyalty; Repurchase intention partially mediates the effect of customer experience on consumer loyalty; and Repurchase intention partially mediates the effect of trust on consumer loyalty. The results of this test explain that the loyalty increase model for Shopee consumers in Banda Aceh City is a function of increasing consumer repurchase interest, increasing customer experience, and strengthening trust in the Shopee brand